An introduction to Mill's utilitarian ethics - West, Henry R. (Cambridge University Press, 2004)
The book serves as both a commentary to and interpretation of the text. It also defends Mill against his critics. An appendix reviews in detail the structure and arguments of Utilitarianism. This book is primarily intended as a textbook for students in philosophy assigned to read Utilitarianism but it should also prove helpful to students and professionals in other fields such as political science, history and economics.